Female leaders in the 21st century in a masculine world - Kessler, Martina (Koers, 2014)
The 21st century shows an increase in the number of women occupying leadership positions. The challenge is: How do they lead in a context which is still male dominated? Often female leaders simply try to copy the male leadership style they are familiar with. But sometimes, in doing so, they lose their femininity and the organisation misses out on the specific opportunities of female leadership. One aim of this article is to discuss the opportunities and strengths of a female leadership style such as pro-social behaviour and a panorama view. We will also deal with the issue of how women approach power and the power bases women would typically use. One conclusion is that we need the benefits of both male and female leadership for the 21st century